2018
DOI: 10.1523/jneurosci.1627-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Age Differentiation within Gray Matter, White Matter, and between Memory and White Matter in an Adult Life Span Cohort

Abstract: It is well established that brain structures and cognitive functions change across the life span. A long-standing hypothesis called “age differentiation” additionally posits that the relations between cognitive functions also change with age. To date, however, evidence for age-related differentiation is mixed, and no study has examined differentiation of the relationship between brain and cognition. Here we use multigroup structural equation models (SEMs) and SEM trees to study differences within and between b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 60 publications
7
54
0
Order By: Relevance
“…In addition, NAdependent and NA-independent functions, as represented by their respective observed variables, were separable into two distinct factors in younger but not older adults in our sample. One potential explanation for this could be that older adults show greater "age dedifferentiation", whereby correlations among distinct measures of cognitive function become more intercorrelated with age [40][41][42] , possibly related to neuropathological changes 43 ; however, this is not a consistent finding as other studies have also found no evidence for age-related dedifferentiation among cognitive factors 38,44 . A second possible explanation is that although specific cognitive and behavioral functions relying on the LC-NA system have been described, it is conceivable that putatively NAindependent measures such as fluid intelligence, sentence comprehension, and facial recognition might also be reliant on this system due to the widespread distribution of noradrenergic neurons and the role of NA in attention and arousal that underlies diverse tests of cognitive functions.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, NAdependent and NA-independent functions, as represented by their respective observed variables, were separable into two distinct factors in younger but not older adults in our sample. One potential explanation for this could be that older adults show greater "age dedifferentiation", whereby correlations among distinct measures of cognitive function become more intercorrelated with age [40][41][42] , possibly related to neuropathological changes 43 ; however, this is not a consistent finding as other studies have also found no evidence for age-related dedifferentiation among cognitive factors 38,44 . A second possible explanation is that although specific cognitive and behavioral functions relying on the LC-NA system have been described, it is conceivable that putatively NAindependent measures such as fluid intelligence, sentence comprehension, and facial recognition might also be reliant on this system due to the widespread distribution of noradrenergic neurons and the role of NA in attention and arousal that underlies diverse tests of cognitive functions.…”
Section: Discussionmentioning
confidence: 77%
“…In this exploratory analysis, older adults still showed a significant positive relationship between LC CR and the single latent factor, driven by the rostral region (standardized regression coefficient β = 0.157, z = 2.169, p(>|z|) = 0.030 for whole LC, β = 0.192, z = 2.465, p(>|z|) = 0.014 for rostral, and β = 0.114, z = 1.712, p(>|z|) = 0.087 for caudal LC), and the LCsingle latent factor regression paths between older and younger groups remained significantly different. Normalized total brain volume showed a significant negative correlation with age in both groups, and interestingly, was significantly related to the single latent factor in younger (β = 0.157, z = 2.169, p(>|z|) = 0.030) but not older adults (β = −0.051, z = −0.491, p(>|z|) = 0.623), possibly reflecting age-related differentiation within gray and white matter 38 . The main findings also remained unchanged after the addition of the repetition time (TR) group (30 ms or 50 ms) as a covariate on LC CR.…”
Section: Resultsmentioning
confidence: 89%
“…To approximate white matter contributions to fluid and crystallized ability, we analyzed fractional anisotropy (FA; see Wandell, 2016). We based our choice of FA on previous studies of white matter in developmental samples (de Mooij et al, 2018;Kievit et al, 2016). We used FA as a general summary metric of white matter microstructure as it cannot directly discern between specific cellular components (e.g.…”
Section: Neural Measures: White Matter and Fractional Anisotropymentioning
confidence: 99%
“…In this case, gc and gf covariance would increase between childhood and adolescence, potentially indicating a strengthening of the g-factor across age. However, despite its increased attention in the literature, the debate remains unsolved as evidence in support of both hypotheses has been found (Bickley et al, 1995;de Mooij et al, 2018;Gignac, 2014;Hülür et al, 2011;Juan-Espinosa et al, 2000;Tideman and Gustafsson, 2004). Together, this literature highlights the importance of a lifespan perspective on theories of cognitive development, as neither age differentiation nor dedifferentiation may be solely able to capture the dynamic changes that occur from childhood to adolescence and (late) adulthood (Hartung et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such techniques have been used more recently in emerging field such as cognitive neuroscience. High dimensional individual differences in brain structure or function (e.g., volume or activity measures across dozens of regions or even thousands of voxels) are reduced to a smaller number of factors, which are then used, for instance, to study morphological differences in schizophrenia (Tien et al, 1996), how cortical structure relates to behavioural measures (Colibazzi et al, 2008), and to examine age-related differences (de Mooij et al, 2018). However, one key challenge when reducing the dimensionality of such structural (and functional) brain data is that of symmetry: Much like other body parts, contralateral (left/right) brain regions are highly correlated due to developmental and genetic mechanisms which govern the gross morphology of the brain.…”
Section: Introductionmentioning
confidence: 99%